Trends in consumption, nutrition, and poverty - Ahmed, Akhter (International Food Policy Research Institute, 2000)
Foodgrain consumption dominates household spending in Bangladesh. On average, rice and wheat consumption accounts for 50 percent of total household expenditure, with this share rising to 64 percent for the poorest households (BBS 1995). As nutrition, foodgrains dominate to an even greater extent, accounting for nearly 80 percent of all calories consumed—73 percent from rice and about 6 percent from wheat. Thus, foodgrain consumption remains key not only to the evolution of domestic foodgrain prices and markets but also to trends in nutrition and poverty.